(untitled) (Informatica, 2022)
Due to the relatively closed environment, dense personnel, large passenger flow, long line and wide coverage of urban rail transit, it is difficult to prevent terrorism. Identity recognition is a core element of security. The design and study of urban rail transit security system based on face recognition technology is proposed in this paper. Through the study on the face recognition algorithm of intelligent security system in urban rail transit, the related introduction of face recognition technology, and the analysis on the main mode of face recognition, carry out practical application design ideas. The results show that if FAR is set to a very low range, such as 0.1% or even 0.01%, meanwhile FRR can reach a very low level, such as less than 1%, such a system has practical value, otherwise it may face a large number of passenger affairs and complaints to be handled once applied. When FAR is set to 0.1% and N is 1.6 million, FRR can reach 2.1%. However, according to the test, when the picture quality deteriorates, such as when using a Webcam (image captured by a webcam), the FRR will increase by 2 to 3 times. In fact, if Webcam is used for recognition in Mugshot, the lowest FRR of the three top algorithms is only 5.21%.